CURRENT STATUS OF KNOWLEDGE OF SPHINGIDAE LATREILLE, 1802 (LEPIDOPTERA: BOMBYCOIDEA) IN COLOMBIA - Correa-Carmona, Yenny; Vélez-Bravo, Andrés H.; Echeverri, Marta Isabel Wolff (Zootaxa, 2015)
A list of species and a photographic catalog of moths of the family Sphingidae reported for Colombia is presented. Following examination of 1463 specimens deposited in major entomological collections of Colombia, and a review of the literature, 188 species are reported for the country, of which 19 species and Phryxus genus are reported for the first time for Colombia. The genus Xylophanes has the most species recorded and also the most geographical records. The Andean region has the highest number of records. A diagnosis of each subfamily and genus, comments on the biology of many of the reported species and dichotomous keys are also presented.